Remarkable fluorescence enhancement of upconversion composite film and its application on mercury sensing - 徐赛 张艳秋 李香萍 张金苏 孙佳石 程丽红 陈宝玖 (Journal of rare earths, 2017)
To achieve a stable, sensitive, and high-efficiency biological probe, a novel NaYF4：Yb,Er nanocrystals/TiO2 inverse opal composite film was designed by self-assembly and solvent evaporation methods. 32-fold enhanced upconversion（UC） emission was investigated under 980 nm excitation. According to size-dependency, excitation power density-dependency as well as photonic stop band（PSB）-dependency upconversion spectra, the enhancement mechanism of the composite film was put down to the stochastical diffraction of IOPCs multi-layered structure to the excitation laser. On the basis of the enhancement effect of the composite film, energy transfer between upconversion nanoparticles（UCNPs） and quantum dots（QDs）, and the sensitive sensing of CdTe QDs on mercury, the UC composite film was used for sensing of Hg^2＋ in serum. The solid sensor as a mercury detector owns lots of superiorities such as feasible operation, good linear relationship（R=0.997）, low limit of detection（70.5 nmol/L） and thus may have broad prospects in the biosensing field.